CLINICAL DESCRIPTION OF TREATMENT OF PEOPLE WITH CRIMEAN-CONGO HEMORRHAGIC FEVER AS A LITERATURE REVIEW - Hamidova Saodat Khikmatovna (Scholar Express Journals, 2022)
Crimean-Congo hemorrhagic fever virus (CCHF) is a tick-borne virus whose RNA consists of S, L and M segments. The virus can migrate through ticks with animals and migratory birds, and therefore it is possible to study the geographical distribution through genetic analysis [1]. Temporal and spatial analysis of the diversity of virus strains can serve as a key factor for a better understanding of the relationship between seropositivity and mortality [1]. The clinical spectrum of CCHF ranges from mild infections to severe to fatal. According to recent data, in severe cases of CCHF, hemorrhagic manifestations may develop with a mortality rate of 4 to 20%, depending on the geographical region and the quality of medical care [2].
Keywords: Crimean-Congo; virus; understanding; migratory